P23 Using 3-dimensional tumour mapping to study patterns of relapse after pelvic exenteration for gynaecological malignancy. (1st November 2019) - Imseeh, G; Barton, DPJ; Kolomainen, D; Bryan, S; Fernandes, A; Ash, J; Sohaib, A; de Souza, NM; Taylor, A
Abstract : Introduction/Background: Pelvic exenteration (PE) can provide long-term survival for patients with recurrent gynaecological malignancies, but there is a high risk of relapse. To develop evidence-based strategies for post-operative treatment, this study aimed to identify the anatomical regions at highest risk of recurrence and establish the relationship between pre- and post-PE relapse sites by comparing the anatomical overlap in their volumes. Methodology: All patients who underwent PE for gynaecological malignancy between 2006–2017 at the Royal Marsden Hospital were identified. Clinical information, surgical reports, histopathology and imaging data were retrospectively analysed. DICOM data for tumour recurrences were transferred to the Eclipse radiotherapy planning system. Three-dimensional tumour volumes (3DTV) were generated to create cumulative anatomical maps of recurrence on a reference dataset. For patients with locoregional recurrence (LRR), pre-exenteration (pre_3DTV) and relapse (rel_3DTV) tumour volumes were then outlined on co-registered images. Volumes of overlap were calculated to assess relationship to margins (figure 1). Results: 58 patients were evaluated with median age 56 years (27–83). Cervical cancer (43.1%) and squamous histology (56.9%) were the commonest presentations. At median follow up of 59.4 months, 32 patients (55%) had recurrence of which 26 (81%) had LRR. Cumulative anatomical mapping showed 42% LRR occurred centrally, 27% pelvic side-wall (PSW), 23% anterior, 8% posterior and 19% inguinal. After anterior PE, LRR is predominantly central (50%), posterior PE predominantly PSW (50%) and after total PE anterior (40%). 3DTVs were outlined for 21 patients, 15 with close/positive margins. Mean pre_3DTV was 61.2cm 3 (1.4–474.8) and mean rel_3DTV was 70.4cm 3 (1.3–436.6). With 5 mm isotropic expansion of pre_3DTV, there was overlap in 65% cases. Mean overlap volume was 14.3cm 3 (0–138.5). Conclusion: Loco-regional relapse is the dominant pattern of recurrence following exenteration. There is frequently an anatomical relationship between pre- and post-PE relapsed tumour volumes. This suggests additional targeted local therapy such as re-irradiation may improve outcomes Disclosure: Nothing to disclose.